LAND SUITABILITY AND TOURISM PERFORMANCE: UNDERSTANDING THE ECONOMIC BENEFITS THROUGH COMMUNITY ENGAGEMENT AND INVESTMENT STRATEGIES - Ling , Cai; Yusoff, Zaharah Mohd; Adnan, Nor Aizam (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The aim of this research is to investigate the impact of land suitability on tourist performance through the mediating roles of investment strategy and local interaction. The study emphasizes the importance of understanding how environmental, social, and economic matters intertwine to provide sustainable benefits from tourism in Chinese countryside. The data were collected using a structured questionnaire completed by 272 participants of both the local residents and tourists in Huangma Township, Nanchang County, Jiangxi Province. A quantitative design was employed, and data were processed using SmartPLS for analyzing direct and mediating relationships between the proposed model. The empirical results indicate that land suitability has a significant positive impact on tourism performance, investment strategy, and local participation. Moreover, both investment strategy and local participation were found to mediate the relationship between land suitability and tourism performance, which suggests that natural resources must be actively financially and socially mobilized to provide sustainable tourist outcomes. These findings highlight the inter-linkage between environmental resources, strategic investment, and local participation in establishing effective tourism development. With the integration of land suitability, investment strategies, and community engagement in a single framework, this research contributes by establishing new findings on how rural tourist destinations can leverage their natural endowments to guarantee long-term competitiveness and sustainable economic development.